Macrophage CD40 plays a minor role in obesity-induced metabolic dysfunction. - Suzanne A B M Aarts; Myrthe E Reiche; Myrthe den Toom; Linda Beckers; Marion J J Gijbels; Norbert Gerdes; Menno P J de Winther; Esther Lutgens (PLoS ONE, 2018)
Obesity is a low-grade inflammatory disease that increases the risk for metabolic disorders. CD40-CD40L signaling plays a central role in obesity-induced inflammation. Genetic deficiency of CD40L in diet-induced obesity (DIO) ameliorates adipose tissue inflammation, hepatic steatosis and increases insulin sensitivity. Unexpectedly, absence of CD40 worsened insulin resistance and caused excessive adipose tissue inflammation and hepatosteatosis. To investigate whether deficiency of macrophage CD40 is responsible for the phenotype observed in the CD40-/- mice, we generated CD40flflLysMcre and fed them a standard (SFD) and 54% high fat obesogenic diet (HFD) for 13 weeks. No differences in body weight, adipose tissue weight, adipocyte size, plasma cholesterol or triglyceride levels could be observed between CD40flflLysMcre and wild type (WT) mice. CD40flflLysMcre displayed no changes in glucose tolerance or insulin resistance, but had higher plasma adiponectin levels when fed a SFD. Liver weights, liver cholesterol and triglyceride levels, as well as the degree of hepatosteatosis were not affected by absence of macrophage CD40. CD40flflLysMcre mice displayed a minor increase in adipose tissue leukocyte infiltration on SFD and HFD, which did not result in differences in adipose tissue cytokine levels. We here show that loss of macrophage CD40 signaling does not affect obesity induced metabolic dysregulation and indicates that CD40-deficiency on other cell-types than the macrophage is responsible for the metabolic dysregulation, adipose tissue inflammation and hepatosteatosis that are observed in CD40-/- mice.